Brønsted acid-mediated reactions of ynamides - Chen, Yang-Bo; Qian, Peng-Cheng; Ye, Long-Wu (Chemical Society reviews, 2020)
Over the past two decades, the development and application of ynamide chemistry have received more and more attention. Ynamides have proven to be versatile reagents for organic synthesis, and have been widely applied to the rapid assembly of a diverse range of structurally complex N-containing molecules, especially the valuable N-heterocycles. In comparison with the well-established transition metal-catalyzed reactions of ynamides, metal-free ynamide transformations have relatively seldom been exploited. Recently, Brønsted acid-mediated reactions of ynamides represent significant advances in ynamide chemistry. This review summarizes the latest trends and developments of Brønsted acid-mediated reactions of ynamides, including cycloaddition, cyclization, intramolecular alkoxylation-initiated rearrangement, oxygen atom transfer reactions and hydro-heteroatom addition reactions. This review summarizes the latest trends and developments of Brønsted acid-mediated reactions of ynamides, including cycloaddition, cyclization and so on.